Secure Multi-Source Multicast - Cohen, Alejandro; Cohen, Asaf; Medard, Muriel; Gurewitz, Omer (IEEE transactions on communications, 2019)
The principal mission of multi-source multicast (MSM) is to disseminate all messages from all sources in a network to all destinations. MSM is utilized in numerous applications. In many of them, securing the messages disseminated is critical. A common secure model is to consider a network where there is an eavesdropper which is able to observe a subset of the network links, and seeks a code which keeps the eavesdropper ignorant regarding all the messages . While this is solved when all messages are located at a single source, secure MSM (SMSM) is an open problem, and the rates required are hard to characterize in general. In this paper, we consider individual security , which promises that the eavesdropper has zero mutual information with each message individually , or, more generally, with sub sets of messages . We completely characterize the rate region for SMSM under individual security, and show that such a security level is achievable at the full capacity of the network, that is, the cut-set bound is the matching converse, similar to non-secure MSM. Moreover, we show that the field size is similar to non-secure MSM and does not have to be larger due to the security constraint.